Selected legal aspects of management contracts. - Domańska, Anna (Wydawnictwa Politechniki Łódzkiej, 2012)
Management contracts appeared as a form of an enterprise management when the era of market economy had dawned. The issues of management contracts are complex and multidimensional because they include economic, social, and legal aspects. The discussion below concerns selected legal aspects of management contracts which remain at the focus of the interest of private as well as public law. In order to determine the legal character of such contracts, the provisions of the Civil Code were analysed, in particular the freedom to contract, as well as the provisions of the Labour Code within the area of the employment relationship characteristics and taking judgements of the Supreme Court into account. Ultimately, the legal nature of a given management contract depends on the circumstances in a given case. The analysed selected provisions of detailed acts which the legislator regulated management contracts with indicate that these contracts are civil law contracts. From the standpoint of public law, in particular tax law, this decides about the manner of the settlement of income from such contracts with tax authorities. Natural persons providing services in person based on agreements concerning the management of an enterprise, management contracts, or similar agreements are or are not VAT payers depending on the legal relationship within which they provide these services
Keywords: globalization; management; globalizacja; zarządzanie; aspekty prawne; zarządzanie przedsiębiorstwem; gospodarka rynkowa; umowy o zarządzanie; kodeks cywilny